2021
DOI: 10.1155/2021/5909281
|View full text |Cite
|
Sign up to set email alerts
|

Agent-Based Simulators for Empowering Patients in Self-Care Programs Using Mobile Agents with Machine Learning

Abstract: E-health sustainable systems can be optimized by empowering patients in self-care programs through artificial intelligence ecosystems in which both doctors and patients interact in an agile way. This work proposes agent-based simulators as a mechanism for predicting the repercussions of certain self-care programs in certain patients for finding the most appropriate ones. In order to make this easy for both doctors and patients, mobile agents are used to configure an app for each patient, and this app provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Afterward, trust increases their online choice of doctors [ 39 ]. A recent study by Kumar et al [ 40 ] proposed certain agent-based simulators (ABSs), which, joining with machine learning, simulate the consequences of self-care mindfulness programs on emotions and heart rate variability; ABSs send these repercussions to an application, guiding patients in various exercises. Following the trial of this approach, patients demonstrated their positive attitudes toward it in terms of usefulness and ease of use.…”
Section: Theoretical Grounds and Literature Reviewmentioning
confidence: 99%
“…Afterward, trust increases their online choice of doctors [ 39 ]. A recent study by Kumar et al [ 40 ] proposed certain agent-based simulators (ABSs), which, joining with machine learning, simulate the consequences of self-care mindfulness programs on emotions and heart rate variability; ABSs send these repercussions to an application, guiding patients in various exercises. Following the trial of this approach, patients demonstrated their positive attitudes toward it in terms of usefulness and ease of use.…”
Section: Theoretical Grounds and Literature Reviewmentioning
confidence: 99%
“…Pandemic-induced uncertainty and fear among the general population increased stress, anxiety, and depression [ 8 ]. In this context, agent-based simulators (ABSs), as a unique patient-centered tool of e-health, promote self-care mindfulness and have shown promising results [ 9 ]. Combining ABSs with machine learning could significantly improve the wellbeing of patients without direct supervision from physicians.…”
Section: Introductionmentioning
confidence: 99%
“…However, to follow the target person using various cameras, the individual's identity has to be retrieved from the second camera based on the detailed information acquired from the first camera. Re-identification is relatively correlated with a recognition problem [5]. The target person's probing image is provided, and all of their associated identities in a gallery collection are searched.…”
Section: Introductionmentioning
confidence: 99%